The Vulnerability of Community Capitals as a Threat to Orang Kuala Community Development in Malaysia. (29th May 2014) - Amir Zal, W. A.; Omar, Mustaffa; Salleh, Hood; Ab. Halim, Sharina
Community development emphasizes the utilization of community resources, also known as community capitals. However, it is often difficult for the community to access these resources; this difficulty retards development. Such is the predicament faced by the Orang Kuala, for whom coastal changes have resulted in greater difficulty in accessing their community resources. Nor is that the only threat that they face. For affirmation of these threats, this article lists two objectives, that is, to identify the accessibility of marine resources and to explain the types of threats faced by the Orang Kuala. To achieve these objectives, a study was conducted involving 51 household heads and 5 Orang Kuala informants, all of whom are residents of Sungai Layau village in Johor, Malaysia. This study uses a mixed-method approach, the concurrent embedded design, and also interview-based questionnaires and in-depth interviews simultaneously. For the first objective, the results show that the Orang Kuala can still attain community resources in the form of marine products. However, the Orang Kuala faced three types of threats: trends, shocks, and seasonal changes. The most significant threat to the Orang Kuala is the trend, that is, cost of living and social problems. These threats can reduce their chances of acquiring benefits from these community resources. This condition is called "vulnerability of community capitals." The objective of this article is to put forth proposals on how to increase the capacity of community resources for the Orang Kuala so that their community can attain sustainable development. This proposal is based on the reality that the threats facing the Orang Kuala are at a critical level and that they are ready to accept changes.